025 Lifestyle and health related quality of life changes in coronary and high CVD risk patients and their partners attending the MYACTION integrated vascular prevention programme in the community. (22nd September 2015) - Jennings, C S; Jones, J; Mead, A; Connolly, S; Kotseva, K; Holden, A; Fiumicelli, G; Stevenson, J; Hunjan, M; Turner, E; Wood, D A
Abstract : Background: Based on EUROACTION, we developed MYACTION, a novel community-based preventive cardiology programme for the UK NHS. It integrates preventive care of patients with CHD, traditionally managed in hospital programmes, with asymptomatic high risk individuals (eg, those at high total risk of developing CVD identified at Health Checks, or with diabetes) from primary care. It is family focussed and actively recruits the partners of all patients to the programme which includes a professional lifestyle intervention, and appropriate risk factor management, all undertaken in a community leisure facility. Methods: Coronary patients (COR) from hospital and high risk individuals (HRI) with a CVD risk >20% over 10 years from primary care were invited with their partners to attend the programme. The initial assessment (IA) by cardiac specialist nurse, dietitian and physical activity specialist supported by a preventive cardiologist included measurements of dietary habits (Mediterranean diet score:MDS), physical activity (7-day physical activity recall), anthropometry, risk factors and HRQoL (Hospital Anxiety and Depression Scale, Dartmouth Coop and EQ-VAS). The 16-week programme included one to one lifestyle and risk factor management, educational workshops and supervised exercise sessions. All patients and partners had lifestyle and risk factor measurements made at IA and then at end of programme (EOP). Results: Eighty-seven COR (61.3% of those referred) and 119 HRI (72.6%) attended with 93 partners (59.6%). 59 COR (67.8%), 85 HRI (71.4%) and 58 (63.0%) partners attended the EOP. 5 (25%) out of 20 COR, HRI and partners who were cigarette smokers had stopped smoking at EOP. Mean MDS improved significantly in COR +1.56, (95% CI 1.0 to 2.1), HRI + 1.3 (0.9 to 1.7) and partners + 1.4 (1.0 to 1.9). Proportions achieving physical activity guidelines improved significantly in COR + 47.2% (95% CI 31.8 to 62.5), HRI + 54.7% (40.9 to 68.4) and partners + 44.9% (28.9 to 60.9). Mean BMI and waist circumference were significantly reduced in COR: BMI −0.3 (−0.6 to −0.6) and waist −1.0 cm (−2.0 to −0); and HRI: BMI −0.7 (−0.8 to −0.2) and waist −2.4 cm (−3.4 to −1.5); and partners: BMI −0.4 (−0.8 to −0.1) and waist −1.9 (−2.8 to −1.1). Median anxiety scores were significantly reduced in COR: 6 (2.5, 11) to 5 (2, 8) but not in HRI and partners. Median depression scores were significantly reduced in COR: 3 (2, 6.5) to 2 (1, 5) and HRI: 3 (1, 6) to 2 (1, 5). Median total Dartmouth Coop scores were significantly reduced in COR: 21 (17, 27) to 18 (15, 23) and HRI: 18 (15, 22) to 16 (13.5, 20.5). EQ-VAS scores were significantly improved in COR: 70 (50, 80) to 75 (68, 80), in HRI: 72.5 (60, 80) to 77 (70, 88) and in partners: 75 (60, 80) to 80 (70, 90). Conclusions: The MYACTION programme achieved real improvements in lifestyle, obesity management and in patient reported HRQoL outcomes. These results demonstrate that this novel programme is effective in reducing total CVD risk.